2019
DOI: 10.7567/1882-0786/ab2c96
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of (101)-oriented CsPbBr3 thick films with high carrier mobility using a mist deposition method

Abstract: CsPbBr3 is a promising candidate for highly sensitive flat-panel X-ray detectors due to its excellent optoelectronic properties. Thus, a method of preparing thick CsPbBr3 films (> 10 µm) over large areas (> 10 × 10 cm 2) is required. Herein, we report the fabrication of thick CsPbBr3 films using a scalable mist deposition method. In this method, the film thickness was controlled and up-scaled by the number of deposition cycles. The obtained CsPbBr3 films were composed of highly (101)-oriented columnar crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Moreover, it was found that the cooling rate profoundly affect the quality of the as-grown CsPbBr 3 . With a slow cooling rate, the quasimonocrystalline CsPbBr 3 obtained showed rather uniform morphology and a preferred crystal orientation along (101). As a result, it exhibited a high μτ product of 1.3 × 10 −2 cm 2 V −1 , which approached the record value of single-crystalline perovskites reported so far.…”
Section: Lead Based Perovskitementioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, it was found that the cooling rate profoundly affect the quality of the as-grown CsPbBr 3 . With a slow cooling rate, the quasimonocrystalline CsPbBr 3 obtained showed rather uniform morphology and a preferred crystal orientation along (101). As a result, it exhibited a high μτ product of 1.3 × 10 −2 cm 2 V −1 , which approached the record value of single-crystalline perovskites reported so far.…”
Section: Lead Based Perovskitementioning
confidence: 52%
“…A, A photograph of Cs‐MA‐FA perovskite based flexible X‐ray detector; A photograph and the corresponding X‐ray image of an investigated object; Reproduced with permission form Reference 99, Copyright 2020, American Chemical Society 99 ; B, Schematic illustration of the dissolution‐recrystallization approach; Reproduced with permission form Reference 100, Copyright 2019, Wiley‐VCH 100 ; C, Schematic illustration of a ultrasonic‐assisted mist deposition protocol; Reproduced with permission form Reference 101, Copyright 2019, The Japan Society of Applied Physics 101 ; D, Photographs and, E, the cross‐sectional SEM images of CsPbBr 3 grown on ITO and ITO/Polymer; Reproduced with permission form Reference 102, Copyright 2020, Materials Research Society 102 ; F, Schematic diagram of the hot‐pressing protocol; G, A cross‐sectional SEM image of the thick CsPbBr 3 film; H, X‐ray response of the CsPbBr 3 detector with different dose rates at 4.2 V mm −1 ; I, The sensitivity and photoconductive gain and, J, the LoD of the CsPbBr 3 detector as a function of applied bias; Reproduced with permission form Reference 44, Copyright 2019, Wiley‐VCH 44 …”
Section: Materials Engineering Of Perovskite X‐ray Absorbermentioning
confidence: 99%
“…This nonlinear behavior originates from the space-charge-limited current (SCLC) effect that occurs when uncompensated charge carriers are injected into the material from the MSM contacts. In this condition, the mobility (μ) can be approximately estimated in the SCLC region (J ~ V 2 ) under dark conditions by using the Mott–Gurney law [ 52 ]: where is the channel length (20 μm), ε 0 is the permittivity of vacuum, and ε is the relative dielectric constant of CsPbBr 3 , which is in the order of ~24 [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The carrier and dilution gas flow rate were set at 0.375 and 4.625 L min -1 , respectively. The substrate temperature was set at 150 °C optimized for the fabrication of highly (101)-oriented CsPbBr3 films in our previous report [21]. In this study, CsPbBr3 was deposited onto a reduced area of 26 × 10 mm 2 by moving the substrate by 10 mm at a speed of 0.80 mm s -1 .…”
Section: Preparation Of Cspbbr3 Thick Filmsmentioning
confidence: 99%
“…Recently, we reported the fabrication of (101)-oriented CsPbBr3 films with a thickness of up to 28 μm using a mist deposition method, which is suitable for the large area production [21]. Much thicker films (over 100 μm) are preferable to a highly sensitive X-ray detection.…”
Section: Introductionmentioning
confidence: 99%